Escape in the Scroll: Academic Stress and Cyberloafing Behavior among University Students: Stres Akademik dan Perilaku Cyberloafing pada Mahasiswa - Syifa Nur Rohmah; Ummi Barokah; Muhammad Azka Ziyan; Mayla Zahwa Syabania; Ridho Maulana Apriandi (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Cyberloafing, defined as using the internet for non-academic activities during learning, has become a pressing issue in higher education. Guided by the Transactional Model of Stress and Coping (Lazarus & Folkman, 1984), this study examines whether academic stress is positively associated with cyberloafing among students of the Faculty of Da'wah and Communication, Syarif Hidayatullah State Islamic University Jakarta. Using a quantitative causal-associative design, data were collected via an online questionnaire from 91 active undergraduates (cohorts 2021–2024). Academic stress was measured with a modified Student-Life Stress Inventory (Puteri, 2024; α=0.824), and cyberloafing with the Indonesian Academic Cyberloafing Scale (Fuadi et al., 2025; α=0.915). Simple linear regression analysis (SPSS v27) revealed that academic stress significantly predicted cyberloafing (β = .25, SE = .10, t = 2.43, p = .017, 95% CI [.04, .45]), but with a small effect size (R² = 0.062). These results suggest that while academic stress contributes to cyberloafing, the majority of variance is explained by other factors such as self-regulation, motivation, and digital habits. Practical implications include structured tech breaks, phased learning tasks, and self-regulation training to mitigate cyberloafing in academic settings. Future research should employ multivariate models and cross-program replication to better capture the multidimensional drivers of cyberloafing.